Prevalence of peripheral arterial occlusive disease in patients referred to a tertiary care hospital in Salvador, Bahia, Brazil, for coronary angiography - Nunes,J.L.B. (2008)
The presence of peripheral arterial occlusive disease increases the morbidity and mortality of patients with coronary artery disease. The objective of the present study was to calculate the prevalence of peripheral arterial occlusive disease in patients referred for coronary angiography. This prevalence study was carried out at the Hemodynamics Unit of Hospital Santa Isabel, Salvador, Brazil, from December 2004 to April 2005. After approval by the Ethics Committee of the hospital, 397 patients with angiographic signs of coronary artery disease were enrolled. Diagnosis of peripheral arterial occlusive disease was made using the ankle-brachial blood pressure index (£0.90). Statistical analyses were performed using the z test and a level of significance of a = 5%, 95%CI, the chi-square test and t-test, and multiple logistic regression analysis. The prevalence of peripheral arterial occlusive disease was 34.3% (95%CI: 29.4-38.9). Mean age was 65.7 ± 9.4 years for patients with peripheral arterial occlusive disease, and 60.3 ± 9.8 years for patients without peripheral arterial occlusive disease (P = 0.0000003). The prevalence of peripheral arterial occlusive disease was 1.57 times greater in patients with hypertension (P = 0.007) and 2.91 times greater in patients with coronary stenosis ³50% (P = 0.002). Illiterate patients and those with little education had a 44% higher chance of presenting peripheral arterial occlusive disease probably as a result of public health prevention policies of limited effectiveness. The prevalence of peripheral arterial occlusive disease in patients referred to a tertiary care hospital in Salvador, Bahia, for coronary angiography, was 34.3%.